Pathogenic ACVR1R206H activation by Activin A‐induced receptor clustering and autophosphorylation. (18th May 2021) - Ramachandran, Anassuya; Mehić, Merima; Wasim, Laabiah; Malinova, Dessislava; Gori, Ilaria; Blaszczyk, Beata K; Carvalho, Diana M; Shore, Eileen M; Jones, Chris; Hyvönen, Marko; Tolar, Pavel; Hill, Caroline S
Abstract: Fibrodysplasia ossificans progressiva (FOP) and diffuse intrinsic pontine glioma (DIPG) are debilitating diseases that share causal mutations in ACVR1, a TGF‐β family type I receptor. ACVR1 R206H is a frequent mutation in both diseases. Pathogenic signaling via the SMAD1/5 pathway is mediated by Activin A, but how the mutation triggers aberrant signaling is not known. We show that ACVR1 is essential for Activin A‐mediated SMAD1/5 phosphorylation and is activated by two distinct mechanisms. Wild‐type ACVR1 is activated by the Activin type I receptors, ACVR1B/C. In contrast, ACVR1 R206H activation does not require upstream kinases, but is predominantly activated via Activin A‐dependent receptor clustering, which induces its auto‐activation. We use optogenetics and live‐imaging approaches to demonstrate Activin A‐induced receptor clustering and show it requires the type II receptors ACVR2A/B. Our data provide molecular mechanistic insight into the pathogenesis of FOP and DIPG by linking the causal activating genetic mutation to disrupted signaling. Synopsis: Combining biochemistry, live imaging and optogenetics, this study reveals non‐canonical modes of TGF‐β family type I receptor ACVR1 activation by autophosphorylation and clustering, suggesting new mechanistic paradigms for TGF‐β family signaling‐related human diseases. Wild‐type ACVR1 is activated in response to Activin A through transphosphorylation by canonical Activin type I receptors. Mutated ACVR1 R206H autoactivates itself upon Activin A‐induced receptor clustering, conferring extended SMAD1/5 phosphorylation. ACVR1 R206H activation is independent of upstream type II receptor kinase activity. Activin A induces ACVR1 R206H clustering and SMAD signaling in patient‐derived diffuse intrinsic pontine glioma (DIPG) cells. Abstract : Activation of mutated TGF‐β family type I receptors independent of upstream type II receptor kinase activity promotes SMAD signaling in human glioma cells.